(untitled) (Journal of Hama University, 2025)
The research aimed to determine the efficiency of cultivation and production of the irrigated soft wheat crop in Homs Governorate for the year 2024. To achieve this goal, we relied on sample data drawn from farmers in the studied area, the number of whom was (56) respondents, and thus the sampling fraction was about (17.23%). Knowing that the size of the statistical population reached (325) farmers. It was used to carry out descriptive economic analytical research, where the values ​​of productivity and economic indicators were estimated, which were adopted to calculate various types of efficiency. The cultivation and production of the irrigated soft wheat crop in Homs Governorate was specific from the economic point of view, and from the farmer’s point of view . The total economic and commercial efficiency amounted to about )1.38 (and )1.73(, respectively, while the total amounted to: Marketing efficiency, work process efficiency, and irrigation water use efficiency are about )98.03%(, )63959.15( SP/hour of work, and )1748.22( SP/m3, respectively. The break-even productivity and break-even price reached about)1996.43( kg/ha, and )3722.15( SYP/kg, and thus both: the production and price safety limits reached about )32.32%(. The research suggested the need to take government measures to help farmers expand the cultivation and production of irrigated soft wheat in Homs Governorate encourage.